Analisis Penokohan dalam Film Little Mom Sutradara Guntur Soeharjanto - Ayu Syahrina Sinaga (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
Literature is an art in which there are many elements of humanity in literary works, which involve the expression of the human person in the form of experiences, thoughts, ideas, desires, and beliefs in the form of a picture of life. In addition to novels, poetry, short stories and dramas, there are also films, dramas and films are imaginative literary works because films are literary works that reveal stories through the dialogues of their characters. The title of the film taken as the object of research is Little Mom, director Guntur Soeharjanto. The purpose of this study is to identify and analyze the characters and characterizations contained in this film. This study also uses qualitative methods, qualitative methods are methods that use descriptive methods in the form of words or writing in explaining the results of the research. The results of this study indicate that the characters and characterizations in a film are one of the important intrinsic elements in the film, allowing the audience to feel the feelings of the character. The author finds a variety of characters who have different characteristics in the Little Mom movie, there are some characters who have protagonists and some have antagonists.